Character education implementation for students in grade IV SDN 5 Sindangkasih regency of Purwakarta West Java - Sofyan Mustoip (Universitas PGRI Madiun, 2018)
Students are less polite especially to teachers who should be respected. The sense of courtesy can be seen when the students shaking hands to the teacher he met, and say